The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m115.672816
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hydrogen Sulfide with Disulfide and Sulfenic Acid to Form the Strongly Nucleophilic Persulfide

Abstract: Background:Hydrogen sulfide (H 2 S) modulates physiological processes in mammals. Results: The reactivity of H 2 S toward disulfides (RSSR) and albumin sulfenic acid (RSOH) to form persulfides (RSSH) was assessed. Conclusion: H 2 S is less reactive than thiols. Persulfides have enhanced nucleophilicity. Significance: This kinetic study helps rationalize the contribution of the reactions with oxidized thiol derivatives to H 2 S biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
365
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(383 citation statements)
references
References 59 publications
15
365
0
3
Order By: Relevance
“…In the case of higher order polysulfides, the same trend is expected. Importantly, the pK a of an RSSH species is typically 1–2 pK a units lower than the corresponding RSH species 42 (and possibly much lower 32), indicating that reactions with an RSS − leaving group should predominate over a reaction with an RS − leaving group. Thus, an RSS n R ( n > 1) species should be more electrophilic than the corresponding disulfide.…”
Section: The Chemical Biology Of Hydropersulfides and Polysulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of higher order polysulfides, the same trend is expected. Importantly, the pK a of an RSSH species is typically 1–2 pK a units lower than the corresponding RSH species 42 (and possibly much lower 32), indicating that reactions with an RSS − leaving group should predominate over a reaction with an RS − leaving group. Thus, an RSS n R ( n > 1) species should be more electrophilic than the corresponding disulfide.…”
Section: The Chemical Biology Of Hydropersulfides and Polysulfidesmentioning
confidence: 99%
“…These reactions have been studied extensively 21, 22, 31, 32 and they represent possible routes of endogenous hydropersulfide formation. It needs to be mentioned, however, that formation of hydropersulfides via Reaction 1 has been questioned on the basis of the low reducing power of H 2 S, its relatively low concentration and the high concentrations of GSH 33.…”
Section: The Generation and Prevalence Of Hydropersulfides And Polysumentioning
confidence: 99%
“…Additionally, we showed that CysSSH is biosynthesised from cystine by cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE), which in turn may contribute to the production of GSSH and other CysSSH derivatives formed in humans 14 15 18. The antioxidant capacity and reactivity of GSSH and CysSSH are approximately 10–100 times greater than those of GSH and cysteine (CysSH) 14 15 17 19. Currently, the amounts of reactive persulfide and polysulfide species and their biosynthesis in the lungs of patients with COPD remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an appreciation of sulfide signaling, the mechanisms of how H 2 S functions as a signaling molecule remain under investigation (12). Emerging evidence suggests that highly oxidized sulfur species, termed reactive sulfur species (RSS), are the actual sulfide-signaling species (13)(14)(15)(16). These include HS•, cysteine sulfenic acids, cysteine persulfides, glutathione persulfides (GSSHs), and inorganic polysulfide species, which catalyze persulfidation of specific proteins and enzymes (13,(17)(18)(19)(20), although the functional impact of this protein modification is as yet not generally clear (17).…”
mentioning
confidence: 99%